Mars neutron radiation environment from HEND/Odyssey and DAN/MSL observations. (May 2020) - Litvak, M.L.; Sanin, A.B.; Mitrofanov, I.G.; Bakhtin, B.; Jun, I.; Martinez-Sierra, L.M.; Nosov, A.V.; Perkhov, A.S.
Abstract: High Energy Neutron Detector (HEND) onboard the orbital Mars Odyssey mission and Dynamic Albedo of Neutrons (DAN) onboard the Curiosity rover are measuring neutron albedo of Mars produced by Galactic Cosmic Rays (GCR). The numerical simulations of HEND/Odyssey and DAN/MSL and comparison between model predictions and experimental data has been implemented to unfold Mars neutron spectra both on orbit and surface and evaluate biological impact contributed by neutrons. It was found that the maximum neuron equivalent dose rate by neutrons below 10 ​MeV could be as high as 45 ​± ​7 ​μSv per day, which is about 6–7% of the expected charged-particle dose equivalent rate. Highlights: Neutron spectrometers HEND/Odyssey and DAN/MSL were used to study the neutron component of Mars radiation environment. Numerical modeling was implemented to deconvolve neutron spectra in energy range below 10 MeV. .Neutron dose equivalent rate at Gale crater was estimated for the different periods of solar cycle.